Improving Heat Exchange Systems of Turbogenerators for Increase of their Efficiency - Minko A.N.; Shevchenko V.V. (Problems of the Regional Energetics, 2019)
The goal of this work is to define parameters that characterize turbogenerator heat exchanger efficiency and to develop recommendations for its increase by improving the heat exchanger design in different modes and ranges of electromagnetic loads for different cooling medium types (air, hydro-gen, water). The paper uses the results of studies of the thermal state of turbogenerators of foreign and domestic authors, where it is noted that the global economic crisis has complicated the possibility of timely replacement of turbine generators that have expired, therefore partial replacement and/or mod-ernization is most often used. At the same time, in all the electrical engineering plants of the world, the task of increasing the power of turbogenerators is solved without changing their dimensions, which is possible only with the improvement of cooling systems. Therefore, the outer dimensions of the heat exchanger and its connection node to the turbogenerator were preserved in our studies. Gas coolers with different sections and moves number of cooling medium and heat-removing elements arrange-ment were reviewed. Data of TGV-200-550, TA-35-120 turbogenerators were used in calculations. The regime coefficients, that allow to consider the type of cooling medium, thermophysical parame-ters, temperature changes, coolant rate, inlet cooler pressure, number of gas strokes inside the heat ex-changer, cooler tubes’ heat exchange surface area and finning type were introduced. The heat ex-changer thermal stresses were determined depending on the cooler tubes’ geometry and heat exchange surface area in the working temperature range.